2016
DOI: 10.1364/optica.3.000634
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of Gaussian protocols for one-sided device-independent quantum key distribution

Abstract: Nonlocal correlations, a longstanding foundational topic in quantum information, have recently found application as a resource for cryptographic tasks where not all devices are trusted, for example, in settings with a highly secure central hub, such as a bank or government department, and less secure satellite stations, which are inherently more vulnerable to hardware "hacking" attacks. The asymmetric phenomena of Einstein-Podolsky-Rosen (EPR) steering plays a key role in one-sided device-independent (1sDI) qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 73 publications
1
112
0
2
Order By: Relevance
“…As shown in [4], EPR steering is necessary, but not sufficient for 1SDI-QKD. The continuous-variable case was analyzed by Walk et al [34]. In their work, the secret key is encoded in theX quadrature of a field mode j , and a sufficiently strong demonstration of continuous-variable EPR steering from mode i to j bounds the information that an eavesdropper can have about the key, in a way that is independent of the device at mode i, so that a secret key rate obtained using reverse reconciliation is lower bounded by…”
Section: An Asymmetric Systemmentioning
confidence: 99%
“…As shown in [4], EPR steering is necessary, but not sufficient for 1SDI-QKD. The continuous-variable case was analyzed by Walk et al [34]. In their work, the secret key is encoded in theX quadrature of a field mode j , and a sufficiently strong demonstration of continuous-variable EPR steering from mode i to j bounds the information that an eavesdropper can have about the key, in a way that is independent of the device at mode i, so that a secret key rate obtained using reverse reconciliation is lower bounded by…”
Section: An Asymmetric Systemmentioning
confidence: 99%
“…In this framework, the client trusts all of his quantum resources but distrusts the server. EPR-steering has also been utilised for one-sided device-independent quantum key distribution where the 'one-sided' indicates that one of the parties does not trust their device but the other does [18,19]. There have even been experimental demonstrations of cryptographic schemes in this direction [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, as a subchannel discrimination in quantum information [17] or as a resource for secure and one sided quantum key distribution [45,46,47,48]. Recently [1] it has been shown that two way steering is an important resource for secure quantum teleportation of continuous variable systems and in [49] steering inequalities were used for signatures of quantum teleportation for qubits.…”
Section: Introductionmentioning
confidence: 99%